Activin and BMP4 Synergistically Promote Formation of Definitive Endoderm in Human Embryonic Stem Cells123. (22nd March 2012) - Teo, Adrian K. K.; Ali, Yusuf; Wong, Kee Yew; Chipperfield, Hiram; Sadasivam, Akila; Poobalan, Yogavalli; Tan, Ee Kim; Wang, Siew Tein; Abraham, Suman; Tsuneyoshi, Norihiro; Stanton, Lawrence W.; Dunn, N. Ray
Abstract: Human embryonic stem cells (hESCs) herald tremendous promise for the production of clinically useful cell types for the treatment of injury and disease. Numerous reports demonstrate their differentiation into definitive endoderm (DE) cells, the germ layer from which pancreatic β cells and hepatocytes arise, solely from exposure to a high dose of recombinant Activin/Nodal. We show that combining a second related ligand, BMP4, in combination with Activin A yields 15%–20% more DE as compared with Activin A alone. The addition of recombinant BMP4 accelerates the downregulation of pluripotency genes, particularly SOX2, and results in upregulation of endogenous BMP2 and BMP4, which in turn leads to elevated levels of phospho‐SMAD1/5/8. Combined Activin A and BMP4 treatment also leads to an increase in the expression of DE genes CXCR4, SOX17, and FOXA2 when compared with Activin A addition alone. Comparative microarray studies between DE cells harvested on day 3 of differentiation further reveal a novel set of genes upregulated in response to initial BMP4 exposure. Several of these, including APLNR, LRIG3, MCC, LEPREL1, ROR2, and LZTS1, are expressed in the mouse primitive streak, the site of DE formation. Thus, this synergism between Activin A and BMP4 during the in vitro differentiation of hESC into DE suggests a complex interplay between BMP and Activin/Nodal signaling during the in vivo allocation and expansion of the endoderm lineage. STEM CELLS 2012; 30:631–642